Research on Natural Human-Computer Interaction in Virtual Roaming. (April 2020) - Li, Fuyun; Feng, Jianping; Fu, Mousong
Abstract: With the development of computer technology, human-computer interaction technology has gone through the development process of "command line interface", "graphical user interface" and "natural user interface". This paper explores the use of low-cost Kinect body sensor, in close to the premise of people's habits, let users interact with the virtual scene roaming system in a natural way. Using the Kinect skeleton tracking technology, human posture is recognized through the relative position between joint points, and four kinds of self-defined postures are used to control the change of camera's view angle to realize virtual scene roaming. The algorithm of this method is simple, it realizes the natural interaction between human and computer, and provides reference for the development of related systems in the future.